Postgraduate course for stomatologists about medical emergencies during professional practice - Isis Anastasia Rojas Herrera (Medisan, 2024)
Introduction: During stomatological practice, medical emergencies can be presented related to the procedures carried out or the patients' underlying diseases; however, there are deficiencies in the care to them.